2021
DOI: 10.52804/ijaas2021.229
|View full text |Cite
|
Sign up to set email alerts
|

Genetic variability studies in cherry tomato for growth, yield, and quality traits in open field conditions

Abstract: The goal of this study was to learn more about the nature and extent of genetic diversity, heritability, and genetic progress in cherry tomatoes for various growth, yield, and quality traits. Ten diverse lines of cherry tomato were crossed in diallel fashion (excluding reciprocals) and evaluated for genetic variability studies in open field conditions. The experimental findings revealed that the phenotypic variation and the genotypic variation were equal in magnitude for all the traits indicating less influenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
9
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 4 publications
5
9
1
Order By: Relevance
“…The number of clusters had a positive and significant correlation with the number of fruits per plant (0.45), fruit length (0.17), number of locules (0.19) and TSS (0.15), but a negative significant correlation with average fruit weight (- 0.17). These outcomes are in conformity with the findings of Hussain et al (2021) and Nevani and Sridevi (2021). The number of fruits per cluster had a significant positive correlation with the number of fruits per plant (0.37) negative correlation with average fruit weight (-0.22) and pH of fruit juice (0.15).…”
Section: Correlation Studiessupporting
confidence: 92%
See 1 more Smart Citation
“…The number of clusters had a positive and significant correlation with the number of fruits per plant (0.45), fruit length (0.17), number of locules (0.19) and TSS (0.15), but a negative significant correlation with average fruit weight (- 0.17). These outcomes are in conformity with the findings of Hussain et al (2021) and Nevani and Sridevi (2021). The number of fruits per cluster had a significant positive correlation with the number of fruits per plant (0.37) negative correlation with average fruit weight (-0.22) and pH of fruit juice (0.15).…”
Section: Correlation Studiessupporting
confidence: 92%
“…Fruit diameter had a significant positive correlation with rind thickness (0.16) and number of locules (0.27). Other studies reported by Hussain et al (2021) and Begum et al (2022) support these findings.…”
Section: Correlation Studiessupporting
confidence: 75%
“…It varied from 8.76mg/100g to 55mg/100g. Similar reports on the variations in the lycopene content, TSS and ascorbic acid content are reported byBose et al (2002);Collins and Veazie (2006) andPanthee et al (2012) Hussain et al (2021). reported that the PCV and GCV for total Soluble Solids ( 0 Brix) ranged from 6.86 to 48.78 for reducing sugar (%).…”
supporting
confidence: 84%
“…Fruit color varied from deep red to light yellow. Study conducted byHussain et al (2021) also indicated that the PCV and GCV were found to be higher for Brix and 6.05 0 Brix). The ascorbic acid levels were very high in some of the accessions.…”
mentioning
confidence: 84%
“…The genotypic and phenotypic coefficients of variability, h 2 , and genetic advance are essential biometric tools used to assess the genetic divergence among the genotypes ( Mohamed et al, 2012 ; Pooja et al, 2022 ; Sahoo et al, 2022 ). Genetic variability is the basis for any selection strategy because the larger the genetic variability in the existing population, the greater will be the scope of selection for the improvement of genotypes for the given traits ( Mohamed et al, 2012 ; Hussain et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%